Hubungan Spastisitas dengan Kemampuan Motorik Ekstremitas Atas dan Kemandirian Activity of Daily Living (ADL) Pasien Pasca Stroke Iskemik - Kurniawan, Hendri; Sutopo, Haris (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Stroke causes changes in muscle tone, which are thought to affect limb function (motor skills) and the ability to perform daily activities or activities of daily living (ADL). However, the extent to which spasticity is related to motor skills and ADL independence requires further study. Objectives: The study aims to examine the correlation between spasticity and upper extremity motor skills and independence in performing ADL in ischemic stroke patients. Methods: The study used an observational quantitative method with a cross-sectional design. The study was conducted in the hospital's occupational therapy unit. The sampling technique used purposive sampling technique. The research variables were measured using the Ashworth scale, Fugl-Meyer assessment (FMA), and Barthel Index Modified. Analysis of research data using a correlational test using the SPSS version 20 program. Results: The research subjects were 34 people, with a percentage of each gender of 50%, and generally experienced a stroke <6 months. The majority of research subjects experienced spasticity at level 2 on the Ashworth scale (61.77% -70.59%), experienced moderate upper limb motor disorders (61.77%), and the level of ADL independence at the level from moderate dependence (41.18%) to severe (50%). The results of the correlation test of the level of spasticity with upper limb motor skills showed a correlation coefficient (r) = -0.407 - -0.424 with a p-value = 0.012 - 0.017, while the level of spasticity with the level of ADL independence showed a correlation coefficient (r) = -0.459 - -0.552 with a p-value = 0.002 - 0.006. Conclusion: The level of spasticity was significantly negatively correlated with the level of upper extremity motor ability and the level of ADL independence, with a correlation strength at a moderate level. Keywords : stroke, spasticity, motoric, ADL